(untitled) (Al-Qamar, 2022)
Throughout the history of mankind, one has found evidence of motifs scratched out or painted on cave walls and on various artifacts, closely associating with the immediate surroundings of people who left behind those traces. Likewise, motifs used by artists may hold significance to their immediate surroundings. A look into the reoccurring symbolic motif of the water buffalo ubiquitous in Pakistan by two artists gives variegated points of view. The article aims to situate the work in an original art context to connect two Pakistani Artists, Ghulam Rasul (1942- 2009) and Huma Mulji (1970) separated by a generation. (fig.1) It consists of a short monograph. It relies mainly on the direct study of one painting and an interview with Ghulam Rasul in 2009, considered significant because this painting triggered Ghulam’s career into fame and because the subject matter of the buffalo stands as symbolic to Punjab. An investigation of the path Ghulam Rasul followed leads the research to the artwork produced by Huma Mulji, who has likewise used the buffalo motif. It concurs ideas from two different art movements, Modern Art and Contemporary Art in Pakistan. It puts in evidence the synthesis of Western Art with Pakistan Art and denotes the ever-present exchange of ideas and motifs from around the world.